Pendekatan Maqasidi dalam Interpretasi Ayat-Ayat Riba Pada Analisis Tafsir Ibn Ashur dan al-Maraghi - Muzayanah (Program Pascasarjana IIQ Jakarta, 2024)
This research aims to analyze the interpretation of riba verses from a fiqh perspective using the maqasidi approach in the interpretations of Ibn Ashur and al-Maraghi. Usury as a controversial topic in Islamic teachings, especially in the context of modern economics, requires a deep understanding of fiqh and maqasid al-syari'ah (the goals of sharia). This research uses the library research method, which means reviewing existing literature, especially the tafsir of Al-Maraghi and Ibn Ashur. This research will identify how the two mufassir, Ibn Ashur and al-Maraghi, interpreted verses relating to usury using maqasid principles, such as justice, the benefit of the people, and protection of individual economic rights. Al-Maraghi emphasized that usury transactions, including those carried out in the conventional banking system that involve interest, are expressly forbidden in Islam. Al-Maraghi considers that usury causes injustice in economic transactions, creates an unfair burden on weaker parties, and is detrimental to overall social welfare. However, in cases of emergency or compulsion, when a Muslim has no other choice but to engage in riba transactions to survive, then such transactions may be temporarily permissible.Ibn Ashur emphasized that financial transactions must be carried out with the principles of justice and the welfare of the people, as exemplified in the Islamic economic system which is free from usury and detrimental practices. This paves the way for efforts to establish financial institutions in accordance with Islamic law, which not only pay attention to material benefits, but also provide a positive impact on society as a whole.